Impedance characteristic of shoulder and elbow joints during passive movement - Rahman, Md. Mozasser; Rahman, Mohammad Habibur; Ikeura, Ryujun (2006)
This paper describes the impedance characteristic of shoulder and elbow joints of human arm during passive movement. The arm was moved in a desired trajectory. The motion was actuated by a 1 degree-of-freedom robot system. Trajectories used in the experiment were minimum jerk (the rate of change of acceleration) trajectories, which were found during human and human cooperative task and optimum for muscle movement. As the muscle is mechanically analogous to a spring-damper system, a second-order equation was considered as the model for arm dynamics. In the model, inertia, stiffness and damping factor were considered. The impedance parameters were estimated from the position and torque data obtained from the experiment and based on the “Estimation of Parametric Model”. It was found that the inertia is almost constant over the operational time. The damping factor and stiffness were high at the starting position and became near to zero after 0.4 second.